Mineralogical studies of plagioclase feldspar in Kadavur Anorthosite Complex, Tamilnadu - Kumar, M.Vinoth; Kumar, R. S.; Rajaprian, K.; Singh, Kuldeep (International Journal of Advanced Geosciences, 2014)
The differences in the type of plagioclase twinning in igneous and metamorphic rocks are described. Plagioclase twins are divided, from a Petrological point of view, into the c-twin and the A-twin. Frequencies of the twinned plagioclase and twin types in various endogenous rocks are described and the genesis of the C-twin which characterizes the volcanic and plutonic rocks is interpreted. Lastly, a plagioclase twin method for determining the origin of various granitic rocks is proposed and discussed. Extremely dense Carlsbad twins at the unit-cell scale indicate that additional energy caused by the Carlsbad twin boundaries in highly disordered anorthite is lower than that caused by albite twin boundaries. We propose that for anorthite with an initially disordered structure the total energy induced by Carlsbad twinning is lower than that caused by albite twinning and higher than that caused by albite twinning in anorthite with an initially ordered structure. Keywords: Mineralogical Studies, Plagioclase Twinning Law, Kadavur Anorthosite Complex.